2021
DOI: 10.3389/fmed.2021.639970
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/Ritonavir and Darunavir/Cobicistat in Hospitalized COVID-19 Patients: Findings From the Multicenter Italian CORIST Study

Abstract: Background: Protease inhibitors have been considered as possible therapeutic agents for COVID-19 patients.Objectives: To describe the association between lopinavir/ritonavir (LPV/r) or darunavir/cobicistat (DRV/c) use and in-hospital mortality in COVID-19 patients.Study Design: Multicenter observational study of COVID-19 patients admitted in 33 Italian hospitals. Medications, preexisting conditions, clinical measures, and outcomes were extracted from medical records. Patients were retrospectively divided in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The same tendency was shown in patients in need of ICU admission. Castelnuovo et al 2021 have shown that in addition to advanced age, conditions such as hypertension, underlying cardiovascular, pulmonary, or renal disease strongly influence patient outcome [28]. Our data also confirm the findings of a large-scale study in 10,021 hospitalized patients showing that pre-existing chronic pulmonary diseases are more frequent in patients needing invasive ventilation [6].…”
Section: Risk Stratificationsupporting
confidence: 86%
See 2 more Smart Citations
“…The same tendency was shown in patients in need of ICU admission. Castelnuovo et al 2021 have shown that in addition to advanced age, conditions such as hypertension, underlying cardiovascular, pulmonary, or renal disease strongly influence patient outcome [28]. Our data also confirm the findings of a large-scale study in 10,021 hospitalized patients showing that pre-existing chronic pulmonary diseases are more frequent in patients needing invasive ventilation [6].…”
Section: Risk Stratificationsupporting
confidence: 86%
“…The observed improvement in subjective assessment is probably attributable to radiologists' increasing experience with the interpretation of imaging findings in COVID-19 patients and the use of structured reporting. Various studies show that structured reporting can help to install a baseline in reporting and thus enhance diagnostic performance (28). Therefore, it is reasonable to assume that well-trained radiologists, working in a level-1 center with high case numbers of COVID-19 patients, can achieve a performance comparable to that of the SSQ method.…”
Section: Diagnostic Performancementioning
confidence: 99%
See 1 more Smart Citation
“… 49 , 205–212 A study of darunavir/cobicistat actually showed an increased mortality rate. 213 However, this was an observational study that may have been affected by confounders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent assessment of fatality rates between first and second waves in Italy showed that they were comparable [28]. Nonetheless, we cannot rule out that improvement in COVID-19 treatment may have decreased mortality during the pandemic, especially in the second wave, despite the lack of fully effective treatments [29][30][31]. Finally, vaccination had no role in curbing either of the two waves analyzed here, since almost no vaccine doses were administered in Italy in 2020.…”
Section: Discussionmentioning
confidence: 72%